Taxonomic history of species without subgeneric placement in the genus Wyeomyia Theobald (Diptera: Culicidae) and recognition of Wy. compta Senevet & Abonnenc as a junior synonym of Wy. argenteorostris (Bonne-Wepster & Bonne) - Pereira, Nascimento; Talaga, Stanislas; Guimarães, Anthony Érico; Lourenço-De-Oliveira, Ricardo; de Albuquerque Motta, Monique (Zootaxa, 2019)
The mosquito genus Wyeomyia (Diptera: Culicidae) includes 17 subgenera and 140 species, 30 of which are without subgeneric placement. The taxonomic history of the unplaced species is summarized and the validity of Wy. compta Senevet & Abonnenc is discussed based on examination of the type material. It is clear that the description of Wy. compta was based on specimens belonging to two different species. The holotype adult female is identical to Wy. argenteorostris (Bonne-Wepster & Bonne) whereas the characters described from a larval exuviae mounted on the same slide with the holotype of Wy. albocaerulea Senevet & Abonnenc coincide with those which characterize the subgenus Dodecamyia. Since the larval exuviae cannot be definitely associated with the holotype female and it belongs to either Wy. aphobema Dyar or another species of the subgenus Dodecamyia, it cannot be afforded type status. Therefore, Wy. compta is synonymized with Wy. argenteorostris.